KETIDAKLAZIMAN KOLOKASI PEMBELAJAR BIPA DAN IMPLIKASINYA TERHADAP PEMBELAJARAN BAHASA - Mashadi Said (Jurnal Cakrawala Pendidikan, 2010)
Abstract: Unacceptable Collocations by Learners of Indonesian as a ForeignLanguage and the Implication in Language Learning. Foreign language learnersability to collocate words that are natural and acceptable in the target language isimportant in foreign language learning; however, it is notoriously difficult forforeign language learners and sometimes makes them frustrated. This studyattempts to describe the negative transfer of English collocations into Indonesiancollocations made by learners of Indonesian as a foreign language in their writingassignments. This study employed a qualitative descriptive method. The data werecollected from 36 writing assignments by 12 learners whose mother tongue isEnglish. They were trainee teachers with experience in teaching Indonesian inAustralia. The finding shows that there are 176 unnatural Indonesian collocations,some of which are negative transfers of learners mother tongue. This suggests thatdirect teaching of collocations should be given special emphasis in teachingIndonesian as a foreign language.Keywords: collocation, lexical collocation, grammatical collocation, languagelearning